Limited role of interferon-kappa (IFNK) truncating mutations in common variable immunodeficiency. (August 2017) - Atschekzei, Faranaz; Dörk, Thilo; Schürmann, Peter; Geffers, Robert; Witte, Torsten; Schmidt, Reinhold E.
Highlights: Whole exome sequencing was performed to determine the genetic background of common variable immunodeficiency in two non-consanguineous German families. IFNK was found as the only candidate gene that harbored truncating mutations in affected members from both families. Whole coding region of IFNK was sequenced in a further series of 167 CVID patients and 192 healthy controls, using Sanger sequencing. No additional truncating variants were found. Abstract: We used whole exome sequencing to determine the genetic background of CVID in two non-consanguineous German families. We identified IFNK (interferon-kappa) as the only candidate gene that harbored truncating mutations in affected members from both families. One family segregated c.30_31insTGTT, a known frameshift variant, while the other family segregated the novel IFNK mutation p.K199X that creates a premature stop codon. We sequenced the whole coding region of IFNK in a further series of 167 CVID patients and 192 healthy controls. Frameshift mutation c.30_31insTGTT was identified in 12 cases and 17 controls (OR 0.79, 95% CI 0.33–1.81, p = 0.79), whereas the p.K199X mutation remained restricted to the original family. No additional truncating variants were found. We conclude that, given their frequent occurrence in non-diseased family members and controls, it is unlikely that truncating variants in IFNK constitute a major factor in the development of CVID.